A numerical approach to bio-mechanics analysis based on live micro-CT images in the rat temporomandibular joint - Chia-Chun Chen; Tran-Thi-Ngoc Trang; Ding-Han Wang; Nien-Ti Tsou (Computational and Structural Biotechnology Journal)
Mandible bone is one of the most important parts, as it has a complex structure of trabecular bone and its motion involves both hinge and sliding caused by multiple surrounding muscle loads. However, the numerical models reported in the literature typically adopt uniform bone properties and oversimplify loading conditions. In this study, a finite element model of a rat's mandible was built based on micro-CT images at three different resolutions (20 um, 40 um, and 80 um). The material properties of each element in the model, such as density and Young's modulus, were mapped and assigned based on the brightness of the micro-CT images in the corresponding position, revealing the detailed trabecular bone structure in the model. In addition, eight loads corresponding to the surrounding muscles were applied as boundary conditions to simulate the chewing condition of the rat according to anatomy and experiments. The stress distribution of the mandible and temporomandibular joint can then be determined, having a very good agreement with that observed in the change in bone morphology. The numerical results calculated by the models generated from the micro-CT images of three different resolutions were also analyzed, suggesting the most suitable image resolution for the rat's mandible. The current work provided a novel workflow to generate a more bio-realistic numerical model with high validity.